Exploratory survey about dietary supplement use: a hazardous and erratic way to improve one’s health? (Swiss Medical Weekly, 2013)
INTRODUCTION: Dietary supplement (DS) use increased rapidly in recent years. However, evidence of benefits of many DSs for healthy users is scarce and may not equate with known risks of overdose, drug interaction and recently discovered negative long-term effects. This exploratory study aimed to investigate the perceptions and motivations of DS users in Lausanne, Switzerland. METHOD: A convenience sample (n = 147) was recruited at the entrances of local sales points. Data were collected in on-site semistructured interviews that assessed dietary supplementation habits. RESULTS: The majority of DSs were all-in-one products, containing a mixture of minerals and vitamins, or products containing only minerals. Among the 147 users, 72 (49%) used one all-in-one product and 3 (2%) used two all-in-one products. Thirty-one (21%) consumers did not know for at least one product what the purpose of their DS use was. Seventy-five percent of participants thought that DS use presents no risk or nearly no risk. Only 49% of participants stated that their physicians were informed about their consumption. Although men searched more often for potential risks (p